1991
DOI: 10.3109/02699059109008100
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual and psychosocial sequelae of closed head injury

Abstract: A series of 36 patients who had been hospitalized following closed head injury (CHI) were followed up 4.06 (SD 3.71) years after the injury. Measures were taken of degree of psychosexual dysfunction (Golombok Rust Inventory of Sexual Satisfaction-GRISS), general psychiatric morbidity (General Health Questionnaire-GHQ), and clinical anxiety and depression (Hospital Anxiety and Depression Scale-HAD). These measures were completed by patients and partners. Resulting data revealed that 50% of male patients with cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 27 publications
3
40
0
3
Order By: Relevance
“…The annual direct and indirect monetary burden of TBI on the United States was estimated at $60 billion in 2000 (Finkelstein et al, 2006). Survivors of TBI have a reduced QOL, as assessed by multiple scales, including the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), the Sickness Impact Profile and the General Health Questionnaire, the Life Satisfaction Inventory, and the newlydeveloped Quality of Life in TBI or QOLIBRI scale (Colantonio et al, 1998;Corrigan et al, 1998;Findler et al, 2001;Guilfoyle et al, 2010;Kinsella et al, 1989;Kreuter et al, 1998;O'Carroll et al, 1991;Paniak et al, 1999;Resch et al, 2009;Temkin et al 1988;Truelle et al, 2010). There has been a call for increased utilization of CER to improve these statistics, though such studies in the TBI field have heretofore been limited due to the lack of QOL values for comparing intermediate outcomes as described by the GOSE.…”
Section: Discussionmentioning
confidence: 99%
“…The annual direct and indirect monetary burden of TBI on the United States was estimated at $60 billion in 2000 (Finkelstein et al, 2006). Survivors of TBI have a reduced QOL, as assessed by multiple scales, including the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), the Sickness Impact Profile and the General Health Questionnaire, the Life Satisfaction Inventory, and the newlydeveloped Quality of Life in TBI or QOLIBRI scale (Colantonio et al, 1998;Corrigan et al, 1998;Findler et al, 2001;Guilfoyle et al, 2010;Kinsella et al, 1989;Kreuter et al, 1998;O'Carroll et al, 1991;Paniak et al, 1999;Resch et al, 2009;Temkin et al 1988;Truelle et al, 2010). There has been a call for increased utilization of CER to improve these statistics, though such studies in the TBI field have heretofore been limited due to the lack of QOL values for comparing intermediate outcomes as described by the GOSE.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found erectile dysfunction to be common among men with TBI [14,[25][26][27]. Other frequent difficulties include decreased frequency of sexual activity [14,28] and loss of sexual desire [29,30]. In a review of the literature on sexual functioning following TBI, Aloni and Katz [24] outlined that sexual difficulties following TBI can be attributed to both primary and secondary dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…More formal findings have indicated that 50-60% of people report some level of disruption to sexual function post-TBI [7][8][9][10]. The reasons for changes in sexuality are complex and multifaceted, but TBI has the potential to disrupt social and relationship skills, body image and self-esteem, behavioural control, libido and the physical capacity to perform sexually [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%